A suppression method against range deception jamming based on homologous localisation test. Issue 20 (22nd August 2019) - Huang, Datong; Cui, Guolong; Ge, Mengmeng; Yu, Xianxiang; Kong, Lingjiang
Abstract : In this article, an anti‐jamming technique based on homologous localisation test in multi‐static radar system is proposed to counter multi‐range‐false‐target deception jamming. At first, pre‐process is implemented in each receiver to group the targets that locate in the same direction and improve the accuracy of angle measurement. Then, the localisation of bistatic radar system is performed. Finally, homologous localisation test is implemented in fusion centre by using the localisation results from all the receivers. Simulation results demonstrate that the proposed suppression method can discriminate false targets effectively and realise the localisation of the true target.